212k views
3 votes

16y ^(5) - 12y ^(4) + 4y \\ \\ 64 a * ^(2) - 49ay ^(2)
Plss answer this


1 Answer

6 votes

Answer:

see explanation

Explanation:

Assuming you require to factorise the expressions

16
y^(5) - 12
y^(4) + 4y ← factor out 4y from each term

= 4y(4
y^(4) - 3y³ + 1)

--------------------------------

64ax² - 49ay² ← factor out a from each term

= a(64x² - 49y²) ← this is a difference of squares and factors in general as

a² - b² = (a - b)(a + b) , then

64x² - 49y²

= (8x)² - (7y)²

= (8x - 7y)(8x + 7y)

then

64ax² - 49ay² = a(8x - 7y)(8x + 7y)

User Tkbx
by
5.0k points